Recent Insights into the Role of Hypothalamic AMPK Signaling Cascade upon Metabolic Control - Claret, Marc; Schneeberger, Marc (Frontiers in Neuroscience, 2012)
In 2004, two seminal papers focused on the role of AMP-activated protein kinase (AMPK) in the hypothalamus opened new avenues of research in the field of the central regulation of energy homeostasis. Over the following 8 years, hundreds of studies have firmly established hypothalamic AMPK as a key sensor and integrator of hormonal and nutritional signals with neurochemical and neurophysiological responses to regulate whole-body energy balance. In this review article we aim to discuss the most recent findings in this particular area of research, highlighting the function of hypothalamic AMPK in appetite, thermogenesis and peripheral glucose metabolism. The diversity of mechanisms by which hypothalamic AMPK regulates energy homeostasis illustrates the importance of this evolutionary-conserved energy signaling cascade in the control of this complex and fundamental biological process.